RELATIONSHIPS BETWEEN DECIDUOUS TEETH PREMATURE LOSS AND MALOCCLUSION INCIDENCE IN ELEMENTARY SCHOOL IN CIMAHI - Hillda Herawati; Novita Sukma; Rainisa Dewi Utami (Universitas Kristen Maranatha, 2015)
Premature loss of deciduous teeth is defined as the loss of deciduous teeth before they approach the eruption of the permanent teeth. The aim of this study is to find out the relationship between premature loss of deciduous teeth and the malocclusion according to the Angle’s Classification on Elementary School students children in Cimahi. The type of this research is analytic with a cross sectional research design. The samples are 77 students (7-11 year-old). The sampling method is cluster random sampling. The result shows that the prevalence of premature loss of deciduous teeth was 36.4% and the prevalence of malocclusion is 76.62%. Base on Angle’s Classification, it is revealed that 23.4% of the population has normal occlusion. The percentage of Angle’s class I malocclusion is 45,5%, class II is 23.4% and class III is 7.8%. There is a significant relationship between premature loss of deciduous teeth and its malocclusion (p-value = 0,000). It is concluded that all the students have premature loss of deciduous teeth with malocclusion. Keywords: Premature Loss, Deciduous Teeth, Malocclusion